Pharmacotherapy of borderline personality disorder: what has changed over two decades? A retrospective evaluation of clinical practice - Timäus, Charles (BMC Psychiatry, 2019)
BACKGROUND: The purpose of this study was to assess the pharmacological treatment strategies of inpatients with borderline personality disorder between 2008 and 2012. Additionally, we compared pharmacotherapy during this period to a previous one (1996 to 2004). METHODS: Charts of 87 patients with the main diagnosis of borderline personality disorder receiving inpatient treatment in the University Medical Center of Goettingen, Germany, between 2008 and 2012 were evaluated retrospectively. For each inpatient treatment, psychotropic drug therapy including admission and discharge medication was documented. We compared the prescription rates of the interval 2008–2012 with the interval 1996–2004. RESULTS: 94% of all inpatients of the interval 2008–2012 were treated with at least one psychotropic drug at time of discharge. All classes of psychotropic drugs were applied. We found high prescription rates of naltrexone (35.6%), quetiapine (19.5%), mirtazapine (18.4%), sertraline (12.6%), and escitalopram (11.5%). Compared to 1996–2004, rates of low-potency antipsychotics, tri−/tetracyclic antidepressants and mood stabilizers significantly decreased while usage of naltrexone significantly increased. CONCLUSIONS: In inpatient settings, pharmacotherapy is still highly prevalent in the management of BPD. Prescription strategies changed between 1996 and 2012. Quetiapine was preferred, older antidepressants and low-potency antipsychotics were avoided. Opioid antagonists are increasingly used and should be considered for further investigation.